1.3k views
5 votes
Please help and show work

Please help and show work-example-1

1 Answer

5 votes

Answer:

28

Explanation:

Given:
$ g(x) = x^2 + 3 $ and
$ h(x) = x - 2 $.

To find the composition of the functions:
$ (g \circ  h)(x) = g(h(x)) $

Here,
$ g(h(x)) = g(x - 2) $


$ \implies (x - 2)^2 + 3 $


$ \implies x^2 -4x + 4 + 3 = x^2 - 4x +7 $

We are to find
$ g(h(7)) $. That is to substitute
$ 7 $ in the place of
$ x $.

We get:
$ (7)^2 -4(7) + 7 = 49 - 28 + 7 = 28 $

User Mathsyouth
by
4.3k points